Impact of Government Policy and Socio-Economic Hardship on Stroke Re-Occurrence - Gordons, Alexander E; Gbonjubola, Yusuff Tunde (Journal of Pharmacy Practice and Community Medicine)
Dear Editor, Recurrent stroke is a major contributor to disability and mortality in patients with stroke.[1] Several studies in western countries have shown that the recurrence risk was 11.2% within 12 months; 15% after 2 year and 9.5% within 5 years.[2-4] However, Africa appears to have the highest incidence, prevalence and case fatality of stroke.[5-9] Recurrent stroke still remains a challenge even with improved neuroimaging, acute stroke management, and disseminated use of secondary prevention.[10] The risk of recurrence of stroke has been earlier associated to previously undetected risk factors that are overlooked due to assumptions made about the etiology. Also, relevant risk factors of stroke recurrence and the recurrence patterns of the different stroke subtypes could be mapped systematically.[11]